Bioenergetic stress potentiates antimicrobial resistance and persistence - Barry Li; Shivani Srivastava; Mustafa Shaikh; Gautam Mereddy; Madison R. Garcia; Eric N. Chiles; Avi Shah; Boatema Ofori-Anyinam; Ting-Yu Chu; Nicole J. Cheney; Douglas McCloskey; Xiaoyang Su; et al. (Nature Communications)
Abstract The bactericidal action of some antibiotics is associated with increased ATP consumption, cellular respiration, and reactive oxygen species (ROS) formation. Here, we investigate the effects of ‘bioenergetic stress’, induced by constitutive hydrolysis of ATP and NADH, on antibiotic efficacy in Escherichia coli. We show that bioenergetic stress potentiates the evolution of antibiotic resistance via enhanced ROS production, mutagenic break repair, and transcription-coupled repair. In addition, bioenergetic stress potentiates antibiotic persistence via the stringent response. We propose a model in which the balance between ATP consumption versus production regulates antibiotic resistance and persistence.